Estimation of Out-of-Pocket Expenditure on Utilization of Delivery and Postpartum Services in Public and Private Health Care Facilities- Study in a Rural District of Pakistan - Sohail, Akhtar (UNIMAS, 2023)
Maternal health is considered a significant public health challenge in most developing countries. Over the last two decades, Pakistan witnessed a significant improvement in maternal healthcare infrastructure and maternal health outcomes during the past two decades. However, persistent urban-rural and socio-economic inequalities exist in access to maternal healthcare services across the country. These inequities are reflected in the utilization of maternal healthcare services and out-of-pocket expenditures (OOPEs) between urban vs. rural women and between the public vs. private healthcare sector. This cross-sectional study was conducted in Rajan Pur, a predominantly rural district in Punjab province. The district's maternal healthcare utilization and outcomes remain lower compared to other districts in the province. The overall objectives of this research were divided into two parts. Part 1 aims to study the utilization pattern and socio-economic factors determining the choice of healthcare institutions for delivery and postnatal care. Part 2 aims to estimate OOPEs on delivery and postnatal care and sources of financing OOPEs. The findings of this study make some significant contributions to understanding OOPEs in utilizing delivery and postnatal care by women in a rural district of Pakistan. The study was based on 368 randomly selected mothers who had childbirths from 1st October to 31st December 2020. Multi-stage random sampling technique was used to select the study participants. The results showed that about two-thirds of mothers preferred public hospitals for most recent delivery. The percentage of cesarean deliveries conducted in private hospitals (43.8%) was 4.7 times higher than in public hospitals (9.3%). This rate is almost three times the WHO recommended limit of 10% to 15%. Further, 70% of mothers who had childbirths in private hospitals sought postnatal care, in contrast to 56% of mothers in the public healthcare sector. The logistic regression analysis results showed that the use of public healthcare facilities for delivery care increases with increasing maternal education, monthly household income, and distance to healthcare facilities. The results also showed that mothers' occupation and distance to healthcare facilities positively influence the decision to utilize public hospitals for postnatal care. About 99% of mothers incurred OOPE during delivery and postnatal care, and the mean OOPE incurred during delivery care was PKR 2840 in public hospitals and PKR 25596.3 in private hospitals. A significant difference in OOPE was observed between public versus private hospitals and normal versus cesarean deliveries. OOPE on cesarean delivery in private hospitals was 2.5 times higher than the public hospitals, whereas OOPE on normal delivery care in private hospitals was 9.5 times higher than OOPE in public hospitals. Overall, the mean OOPE on both delivery and postnatal care sought in public hospitals was PKR 3856.70, and in private hospitals, it was PKR 27288.40. The mothers who availed of postnatal care incurred a mean OOPE of PKR 1022.20 in public hospitals and PKR 1692.10 in private hospitals. The study showed that savings and current income were the primary sources of financing OOPE by 90% of participants. Further, 35% of low-income households borrowed money from friends and relatives to cope with the current expenditure on delivery and postnatal care. The research findings would add a significant dimension to addressing the barriers and challenges affecting the utilization of maternal healthcare services beyond individual and contextual perspectives. The findings of the research would also provide some direction for interventions aimed at scaling up the existing maternal healthcare programs at the district level. Finally, the findings and recommendations drawn from the research would provide some insights to health policymakers and planners in developing an integrated and viable maternal healthcare program in Pakistan.